Early diagnosis of autism in the community is associated with marked improvement in social symptoms within 1–2 years. (August 2022) - Gabbay-Dizdar, Nitzan; Ilan, Michal; Meiri, Gal; Faroy, Michal; Michaelovski, Analya; Flusser, Hagit; Menashe, Idan; Koller, Judah; Zachor, Ditza A; Dinstein, Ilan
It is widely believed that early diagnosis and treatment of autism spectrum disorder is essential for better outcome. This is demonstrated by the American Academy of Pediatrics recommendation to screen all 1.5–2.5-year-old toddlers for autism spectrum disorder. However, multiple longitudinal studies of children diagnosed with autism spectrum disorder at 1.5–6 years of age and treated in community settings have not reported any associations between earlier diagnosis and improved outcome in core symptoms. Here, we quantified Longitudinal changes in core autism spectrum disorder symptoms of 131 children diagnosed at 1.2–5 years of age using the Autism Diagnostic Observation Schedule–Second Edition Calibrated Severity Scores over a 1-2 year period. We examined the prevalence and magnitude of Calibrated Severity Scores changes across children who were diagnosed at different ages. The results revealed that age of diagnosis was significantly correlated with poorer outcome ( r (129) = 0.41, p < 0.001). Approximately 65% of the children diagnosed before 2.5 years of age exhibited improvements in Autism Diagnostic Observation Schedule–Second Edition Calibrated Severity Scores (⩾2 points) in contrast to only 23% of the children diagnosed after this age. Changes in younger children were driven by improvements in social symptoms despite deterioration in restricted and repetitive behaviors. These findings reveal that autism spectrum disorder diagnosis before the age of 2.5 is associated with considerable improvement in social symptoms. We suggest that greater brain plasticity and behavioral flexibility enable younger children to benefit more from autism spectrum disorder interventions even in community settings with heterogeneous services. This motivates further prioritization of early autism spectrum disorder screening as recommended by American Academy of Pediatrics guidelines. Lay abstract: It is widely believed that early diagnosis and treatment of autism spectrum disorder is essential for better outcome. This is demonstrated by the American Academy of Pediatrics recommendation to screen all 1.5–2.5-year-old toddlers for autism spectrum disorder. However, multiple longitudinal studies of children diagnosed with autism spectrum disorder at 1.5–6 years of age and treated in community settings have not reported any associations between earlier diagnosis and improved outcome in core autism spectrum disorder symptoms. In this study, we measured changes in core autism spectrum disorder symptoms over a 1–2-year period in 131 children diagnosed with autism spectrum disorder at 1.2–5 years of age, and treated in the community. The results revealed that children who were diagnosed before 2.5 years of age were three times more likely to exhibit considerable improvements in social autism spectrum disorder symptoms in comparison to children diagnosed at later ages. These results highlight the importance of early diagnosis and treatment of autism spectrum disorder even in community settings with heterogeneous services. In addition, these results motivate further prioritization of universal screening for autism spectrum disorder before 2.5 years of age.